2008
DOI: 10.1111/j.1651-2227.2008.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

A normative sample of isotonic and isokinetic muscle strength measurements in children 7 to 12 years of age

Abstract: All the different strength measures showed almost the same pattern, indicating increased absolute strength values with increasing age and no significant gender differences except for flexion at the age of 11 and 12 years . The association between grip strength, vertical jump and quadriceps strength measured isokinetically was moderate to strong. The back muscle endurance test (The Biering-Sørensen test) showed a great roof effect and should not be included in a test battery for school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 30 publications
6
56
3
4
Order By: Relevance
“…In a preliminary analysis of data obtained in children with end-stage renal disease who have a generalized deficit in muscle strength, we found a very strong correlation between grip strength and total muscle strength (r=0.884, p<0.0001), The second purpose of this study was to provide gender-, age-, height-, and weight-related reference charts for grip strength for Dutch children, adolescents, and young adults. Preliminary analysis showed that our study sample was generally similar in height, weight [18,20,33], and BMI [19,38] compared with other studies, but boys and girls of our study sample were slightly taller and had higher body weight from 13 years onwards. The results of the muscle strength measurements were comparable with previous studies [2,4,11,18,20,24,31], but our results showed, in most cases, a somewhat lower muscle strength, especially after puberty.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a preliminary analysis of data obtained in children with end-stage renal disease who have a generalized deficit in muscle strength, we found a very strong correlation between grip strength and total muscle strength (r=0.884, p<0.0001), The second purpose of this study was to provide gender-, age-, height-, and weight-related reference charts for grip strength for Dutch children, adolescents, and young adults. Preliminary analysis showed that our study sample was generally similar in height, weight [18,20,33], and BMI [19,38] compared with other studies, but boys and girls of our study sample were slightly taller and had higher body weight from 13 years onwards. The results of the muscle strength measurements were comparable with previous studies [2,4,11,18,20,24,31], but our results showed, in most cases, a somewhat lower muscle strength, especially after puberty.…”
Section: Discussionmentioning
confidence: 74%
“…Although several studies are published establishing normative data for muscle strength in children [4,18,24], adolescents, and young adults for different muscle groups, only in a few studies anthropometrical variables were specified [2,11,20,31,41]. Reliable muscle strength measurement of different muscle groups is time-consuming and a quick and simple measurement might provide a good indication of the general muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…The participants were seated on a chair with the shoulder adducted and neutrally rotated. Whereas the forearm and wrist were set in neutral position, the elbow was flexed at 90° ( Gerodimos;Holm et al, 2008). The testing protocol consisted of three maximal isometric contractions for 3 -5 s, on competed hand.…”
Section: Methodsmentioning
confidence: 99%
“…Um mecanismo fisiológico que contribui para a produção de força explosiva é o ciclo de alongamento e encurtamento, responsável por gerar energia elástica a partir da contração muscular excêntrica seguida por uma contração concêntrica 5 . Devido às diversas formas que pode ser manifestada, a força tem sido estudada em crianças por meio de diferentes métodos de avaliação, dentre eles a execução de saltos, levantamento de pesos, dinamômetro hidráulico e isocinético 6 . Os saltos vertical, horizontal e sêxtuplo têm sido utilizados como indicadores da força dos membros inferiores em crianças e adolescentes, uma vez que demonstraram ser sensíveis ao treinamento de força [7][8][9] e ao treinamento específico de modalidade esportiva handebol 10 .…”
unclassified